1997
DOI: 10.1038/sj.bjp.0701517
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mycophenolic acid on TNFα‐induced expression of cell adhesion molecules in human venous endothelial cells in vitro

Abstract: Mycophenolic acid (MPA) is an inhibitor of inosine‐5′‐monophosphate dehydrogenase and therefore interferes with cellular GTP biosynthesis. Recently, MPA has been used as an antiproliferative and immunosuppressive agent. In the present study, the effect of MPA on the expression of the endothelial cell adhesion molecules (CAMs), intercellular (I) CAM‐1, vascular (V) CAM‐1 and endothelial (E)‐selectin, was investigated in tumour necrosis factor‐α (TNFα)‐activated cultured human venous endothelial cells (EC). Surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 29 publications
2
20
0
Order By: Relevance
“…RANTES, was synergistically increased, indicating a possible proinflammatory effect of MMF on RANTES release [9]. In similar manner, in vitro data showed that apart from antiproliferative effects, MMF enhances TNF-induced expression of VCAM-1 and E-selectin on human endothelial cells [10]. The clinical significance of a these findings remains unclear, however, and should be mentioned in association with the data presented here.…”
Section: Discussionsupporting
confidence: 41%
“…RANTES, was synergistically increased, indicating a possible proinflammatory effect of MMF on RANTES release [9]. In similar manner, in vitro data showed that apart from antiproliferative effects, MMF enhances TNF-induced expression of VCAM-1 and E-selectin on human endothelial cells [10]. The clinical significance of a these findings remains unclear, however, and should be mentioned in association with the data presented here.…”
Section: Discussionsupporting
confidence: 41%
“…These results are partly in agreement with the finding of Raab M et al [10] who demonstrated an inhibitory effect of MPA on TNFa-stimulated expression of ICAM-1, VCAM-1 and E-selectin in HUVECs. In contrast, Hauser IA et al [22] showed that MPA increased TNFastimulated expression of VCAM-1 and E-selectin, but not of ICAM-1 in HUVECs.…”
Section: Discussionmentioning
confidence: 89%
“…9 We used promoter arrays to measure the activity of multiple TFs in remodeling ECs after exposure to the angioinhibitory protein pigment epithelial-derived factor (PEDF). We chose nuclear factor-B (NF-B) because it is implicated in angiogenesis, 10 drives Fas ligand (FasL) expression, 11 and is activated by PEDF in non-ECs. 12 NF-B can play 2 opposing roles in tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%